The intravascular ultrasound morphometry of iliac veins in subjects without severe chronic venous insufficiency and its implications for treatment indications and stent size selection. (June 2020) - Dzieciuchowicz, Łukasz; Krzyżański, Radosław; Kruszyna, Łukasz; Krasinski, Zbigniew; Gabriel, Marcin; Oszkinis, Grzegorz
Objectives: The purpose of this study is to report the intravascular ultrasound morphometry of iliac veins and its relation to demographic and anthropometric factors in subjects without chronic venous insufficiency. Methods: Thirty-three patients, without chronic venous insufficiency – qualified to great saphenous vein stripping due to unilateral, primary varicose veins – participated in the study. During the surgery, left and right external iliac veins, common iliac veins and inferior vena cava were interrogated with intravascular ultrasound. The morphometric analysis included measurement of a cross-sectional area at normal, non-stenosed vein segments (ref-CSA) and at the point of the most prominent narrowing (minimal lumen area (MLA)). Based on these measurements, a percentage of stenosis (S%) and calculated lumen diameter of interrogated veins were determined according to the following formulas, S% = (ref-CSA–MLA)/ref-CSA × 100 and CLD = 2 × √(ref-CSA/π), respectively. Results: Median ref-CSA, S% and calculated lumen diameter were 265.3 mm 2, 45.8% and 18.4 mm for inferior vena cava; 193.9 mm 2, 62.4% and 15.7 mm for left common iliac veins; 166.9 mm 2, 35.7% and 14.2 mm for right common iliac veins; 136.5 mm 2, 48.0% and 12.8 mm for left external iliac veins and 140.9 mm 2, 46.3% and 13.5 mm for right external iliac veins. There were statistically significant differences between left and right common iliac veins ref-CSA, common iliac veins S% and common iliac veins calculated lumen diameter (p = 0.03, p < 0 and p = 0.03, respectively). The S% of left external iliac veins was greater in women 52.2 versus 37.2% in men (p = 0.04). Neither age nor anthropometric factors had any influence on the calculated lumen diameter of the analysed veins. A negative correlation between the left common iliac veins S% and the age was observed (p = 0.03). Conclusions: In adult subjects, the calculated lumen diameter of the common iliac veins is greater on the left side and is not influenced by age and body size. Common iliac vein stenosis occurs more frequently on the left side, decreases with age and tends to be more frequent in women.